Pilot Scale Production of Precast Concrete Elements with Wood Biomass Ash - Jelena Šantek Bajto (MDPI AG, 2021)
Downsizing fossil fuel dependence and greenhouse gas emissions is at the forefront of a sustainable future. The expansion of renewable energy while striving to minimize dependence on fossil fuels has led to biomass taking the lead among renewable energy sources, with wood having the broadest application. Along with the growing trend of using biomass as a renewable energy source, the combustion of wood biomass results in wood biomass ash (WBA), leading to compelling amounts of waste. In this study, the technical feasibility of fly WBA from different Croatian power plants was analyzed to evaluate its potential use in precast concrete drainage elements and curb units. By implementing a performance-based design, the influence of various factors in thermal processing of wood biomass was investigated, together with a detailed characterization of WBA in order to assess the feasibility of using WBA as a secondary raw material in a large-scale industrial batching plant. The compressive strength and durability properties (water absorption, permeability, and freeze–thaw resistance) of concrete mixtures with WBA as a replacement for 15 wt% cement were evaluated and compared with the precast concrete manufacturer’s technical requirements. The main concerns identified were compositional inconsistency of WBA, workability downturn, delay in initial reactivity rate, and increased water absorption. Concrete with WBA based on a circular design has been found to be a viable solution to cement depletion, stepping up from recycling to reuse of industrial waste.